2019
DOI: 10.15578/ifrj.25.1.2019.19-26
|View full text |Cite
|
Sign up to set email alerts
|

POPULATION PARAMETERS OF ENDEAVOUR SHRIMP (Metapenaeus ensis de Haan) IN BINUANGEUN AND ADJACENT WATERS, WEST JAVA

Abstract: Study on the population dynamic of endeavour shrimp (Metapenaus ensis) was conducted in Binuangeun waters based on data collected during period of survey, January to November 2016. The purpose of the study was to identify population parameters of the endeavour shrimp. Result showed that the endeavor shrimp growth pattern in Binuangeun waters was negative allometric and sex ratio of males and females was 1.0 : 2.7. The chi square test indicated that comparison of male and female of the endeavour shrimp was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 1 publication
0
2
1
4
Order By: Relevance
“…The length at first maturity (Lm) of the endeavour shrimp in Binuangeun waters was 37.7 mm in carapace length. The Lm value found in this study is slightly higher than those reported for endeavour shrimp of Tanjung Krawang was 20 mm (Martosubroto, 1978), South Coast of Java waters was 36,8 mm (Suman, 1990) and Cilacap waters was 31,80 mm (Suman & Boer, 2005). Nikolsky, (1963) stated that Lm value is influenced by some factors, such as: depth and type of habitat in association with food availability, temperature, and light.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…The length at first maturity (Lm) of the endeavour shrimp in Binuangeun waters was 37.7 mm in carapace length. The Lm value found in this study is slightly higher than those reported for endeavour shrimp of Tanjung Krawang was 20 mm (Martosubroto, 1978), South Coast of Java waters was 36,8 mm (Suman, 1990) and Cilacap waters was 31,80 mm (Suman & Boer, 2005). Nikolsky, (1963) stated that Lm value is influenced by some factors, such as: depth and type of habitat in association with food availability, temperature, and light.…”
Section: Discussioncontrasting
confidence: 59%
“…Catch of endeavour shrimp was the second highest after others s h r i m p (Parapenaeopsis spp.) (Suman, 2004;RIMF, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…This was different from the case in the estuary of Cenranae River, South Sulawesi, where the ratio between male and females was balanced (Gunarto et al, 1999). The cause of the differences in male-female ratios could be due to fishing pressure and migration factors (Suman, 2004;Edrus & Syam, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Besarnya permintaan udang memerlukan adanya informasi ilmiah dan data potensi sumberdaya udang yang lengkap, up to date, dan berkelanjutan dari perairan Meulaboh (Aceh Barat). Penelitian sebelumnya telah dilakukan di perairan yang sama tahun 2009 untuk udang kelong (Penaeus sp) [14] dan penelitian tentang udang dogol (Metapenaeus ensis) di perairan Cilacap dan di perairan Arafura [11]; [10], di perairan Selat Bangka [18], dan di perairan Binuangeun [9].…”
Section: Pendahuluanunclassified